2017
DOI: 10.1038/nrcardio.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes and macrophages in abdominal aortic aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a life-threatening disease associated with high morbidity, and high mortality in the event of aortic rupture. Major advances in open surgical and endovascular repair of AAA have been achieved during the past 2 decades. However, drug-based therapies are still lacking, highlighting a real need for better understanding of the molecular and cellular mechanisms involved in AAA formation and progression. The main pathological features of AAA include extracellular matrix remodelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
321
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(325 citation statements)
references
References 184 publications
(232 reference statements)
3
321
0
1
Order By: Relevance
“…Furthermore, we have only examined in vitro osteoclastogenic changes by culturing and stimulating the RAW 264.7 cell line. It has been reported that most of the macrophages accumulating in the aneurysmal aortic wall derive from circulating monocytes, which are produced in the bone marrow [33]. Therefore, we plan to examine OCG not only in RAW 264.7 cells, but also in bone marrow-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have only examined in vitro osteoclastogenic changes by culturing and stimulating the RAW 264.7 cell line. It has been reported that most of the macrophages accumulating in the aneurysmal aortic wall derive from circulating monocytes, which are produced in the bone marrow [33]. Therefore, we plan to examine OCG not only in RAW 264.7 cells, but also in bone marrow-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, macrophages have a major function in inflammatory progression. Therefore, macrophages may have the chance to become drug carriers (138). A previous study attempted to use the macrophage membrane to deliver nanoparticles (emtansine liposome).…”
Section: Aamentioning
confidence: 99%
“…80 Most of AAA-associated macrophages originate from the circulating blood and seem to Mallat Recent Highlights of ATVB: Macrophages e95 be mobilized from the spleen in a B cell-dependent manner after angiotensin II stimulation. 81 The activation and phenotype of AAA macrophages substantially determines the progression of AAA.…”
Section: Monocytes/macrophages In Abdominal Aortic Aneurysmmentioning
confidence: 99%